Service Quality Perception and its Impact on Internet Banking in Klang Valley - Aseh, Khairi; Pathmanathan, P. Ravindran (Archives of Business Research, 2020)
Banking in Malaysia has undergone rapid transformation over the past two decades, witnessing a maritime shift in the nature of the services offered by banks, which have a positive impact on bank customers. The public sector banks have started to incorporate new technology into their operations with increasing customer expectations. It brought about a change in customer perceptions. Hence to what extent the needs to be studied were satisfied or not satisfied with the consumers. Since the Internet is a new virtual medium with so many potential customers, it is the banks that are most critical to consider customer desires and wants. This study aims to identify the impact of demographic characteristics of respondents on internet banking adoption. A total of 600 respondents from the one of the banks in Kuala Lumpur City who was selected for the purpose of this study. Results on service quality perception and its impact on Internet banking has been discussed in this paper.